The role of polymerization cycle and post-pressing time on tooth movement in complete dentures - Wagner Araujo de Negreiros; Rafael Leonardo Xediek Consani; Marcus Aurelio Rabelo Lima Verde; Antonio Materson da Silva; Lecio Pitombeira Pinto (Sociedade Brasileira de Pesquisa Odontológica, 2009)
This study analyzed the influence of polymerization cycle and post-pressing time on tooth movement in complete dentures. Forty maxillary complete dentures were fabricated and randomly assigned to 8 groups (n = 5); the polymerization cycle (conventional long cycle in water bath, fast cycle in boiling water, and by microwave energy) and the post-pressing time (immediate and 6 hours) were varied. Metal reference pins were placed on the incisal border of the central incisors (RI and LI), on the buccal cusp of the first premolars (RP and LP), and on the mesiobuccal cusp of the second molars (RM and LM). Two transverse and 2 anteroposterior distances were measured with a linear optical microscope (Olympus Optical Co., Tokyo, Japan) with an accuracy of .0005 mm, before and after processing the complete dentures. The data collected were submitted to analysis of variance (ANOVA) and the Tukey Test at a significance level of 5%. When Clássico, a conventional heat-polymerizable acrylic resin, was polymerized by microwave energy, tooth movement was statistically significant for 2 distances, with the highest value being observed for the 6-hour post-pressing time. Onda-Cryl microwave acrylic resin processed by microwave energy presented the lowest tooth movement for 2 distances, considering the 6-hour post-pressing time. QC-20 acrylic resin presented no statistically significant change considering both post-pressing times in each distance evaluated. Tooth movement showed an asymmetric behavior, so the mastering of the processing method is essential to the precise execution of all laboratory steps, irrespective of the polymerization cycle and post-pressing time used.